European Union Regulation on clinical trials and Regulation on medical devices: A common soil for future development - Rasi, Guido; Mugelli, Alessandro (Frontiers in Drug Safety and Regulation, 2022)
The recent European Union (EU) Regulations on clinical trial on medicinal products (MPs) (2014/536) and on medical devices (MD) (2017/745) represent potential improvement for the European health system and may offer advantages to the citizens. As Regulations, they are immediately applicable in Member States overruling national laws, being an advantage for stakeholders (e.g. sponsors and investigators) and Europe becomes de facto one homogeneous place for research and development of medicines and medical devices. This perspective commentary focuses on the most relevant methodological and regulatory aspects of the recent Regulation on clinical trials for drug development and how it may indirectly impact on substance-based medical devices (SBMD). The article highlights the innovations associated with the 2017/745 Regulation, especially to the area of SBMD, which represent a novelty among MDs. Since SBMDs share some aspects of medicines, they will increasingly undergo research in the future related to the performance and safety claims, via post-marketing surveillance. Importantly, SBMD’s Consumers are rapidly increasing due to their usage to treat some common symptoms, which not necessarily need conventional medicines. “Frontiers in Drug Safety and Regulation” created a section to reflect this rapidly-changing scenario and host reports on SBMD in a scientific environment. This initiative is also a reflection of the recent regulation on SBMDs. Thus, the improvement of clinical research through the new EU Regulation on clinical trials may become useful also to the new requirements for SBMD. A novel editorial initiative will further contribute to implement the EU Regulation providing adequate scientific dissemination.